Determinants of mobile money loan disbursements: Evidence from Uganda’s post pandemic digital credit boom - Lorna Katusiime; Frank W. Agbola (PLoS ONE, 2026)
In the aftermath of the COVID-19 pandemic, Uganda witnessed a rapid rise in mobile money usage and digital credit adoption, underscoring the sector’s role in post crisis recovery and financial resilience. Against this backdrop, this paper examines the determinants of mobile money loan disbursements in Uganda a global pioneer in mobile financial innovation, using monthly data from July 2021 to December 2024 and applying the Autoregressive Distributed Lag (ARDL) cointegration framework to capture both long-run relationships and short-run dynamics. Results show a long-run relationship linking average loan disbursements with outstanding loan values and lagged inflation. In the short term, past loan disbursements have a significant impact on current loan values. Behavioural proxies are informative, airtime purchases and timely mobile loan repayments are associated with higher disbursement volumes, consistent with lenders interpreting them as signals of reliability and liquidity. By contrast, higher transaction volumes and fees depress disbursements, underscoring the adverse impact of elevated user costs on credit access. These findings highlight actionable levers for expanding responsible digital credit and deepening inclusion.